Implementation of Bureaucratic Reform Policy at the Investment and One-Stop Integrated Service Office of Malang Regency (Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Malang) - Erdianto Malo, Odniel; Rifai, Muhamad; Indra Gunawan, Cakti (IRDH International Journal of Social Sciences & Humanities, 2025)
In practice, the investment climate in Indonesia is still not conducive, both local and foreign investors remain reluctant to invest capital in various sectors in Indonesia. Several fundamental reasons behind this include complicated licensing processes, inadequate infrastructure quality, many regions that hinder the investment climate, and legal certainty for investors. Therefore, this research aims to determine the policies, impacts of policy implementation, and inhibiting factors in implementing bureaucratic reform policies in the investment sector through DPMPTSP Malang Regency in accelerating the licensing process and increasing investment value. This research uses a qualitative descriptive approach. The data sources used are primary and secondary data. Researchers used observation, documentation, and interviews as data collection techniques. In validating the research results, researchers used the triangulation technique to test the credibility of the research results. The results showed that DPMPTSP of Malang Regency implemented an Online Single Submission (OSS) system to accelerate the licensing process to increase regional investment value; furthermore, a Public Service Mall Building (MPP) was built which aims to integrate services in one place. The impact of these policies has increased the amount of investment in Malang Regency, but the increase is gradual. On the other hand, the overlapping regulations between central and regional governments become inhibiting factors for investors in investing their capital, especially for foreign investors. Based on the research results, the researchers suggest that there needs to be a holistic approach in implementing bureaucratic licensing reform that not only focuses on technological aspects, but also on developing human resource capacity and regulatory harmonization. Development of a comprehensive monitoring and evaluation system to ensure the implementation of bureaucratic licensing reform proceeds according to objectives and delivers positive impacts on increasing investment